A chiral pinwheel supramolecular network driven by the assembly of PTCDI and melamine. - Silly, F; Shaw, A; Castell, M; Briggs, G (2008)
The mixing of perylene-3,4,9,10-tetracarboxylic diimide (PTCDI) and 1,3,5-triazine-2,4,6-triamine (melamine) at room temperature in a ratio of 3 : 4 on Au(111) leads to the formation of a new chiral "pinwheel" structure.